Pengaruh Penambahan Kapur Sirih Terhadap Karakteristik Organoleptik Keripik Kulit Pisang Kepok (Musa Paradisiaca Linn) - Ilma Aenan Hidayah; Melly Fera; Yan El Rizal Unzilatirrizqi Dewantoro (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
Banana is one of the potential tropical fruit commodities in Indonesia, including in Brebes Regency, Central Java Province. So far, people have only used the banana fruit and heart as food processing materials, while banana peels have only been processed product waste. Even though the banana peel contains 18.5% carbohydrates, 68.90% water, some vitamin C, various B-complex vitamins, including B6, fat, lutein, anti-oxidants, calcium, vegetable oil, fiber, serotonin and sufficient protein. With a simple food processing technology, these banana peels can be processed into banana peel chips with sweet, savory and spicy flavors which can be family meals or snacks that have nutritional value and can automatically reduce organic waste and generate income. The purpose of this study was to determine the effect of the addition of whiting on the organoleptic characteristics of banana peel chips. This research was conducted using a quantitative experimental method using a completely randomized design (CRD) with two factors, namely the addition of whiting and soaking time. Parameters measured were acceptability or organoleptic texture, color, aroma and taste.